Pengembangan UMKM dan Pemanfaatan Limbah Sampah Sebagai Industri Kreatif Melalui Kuliah Kerja Nyata di Kelurahan Bagelen - Sarwoto, Sarwoto; Nursaimatussadiya, Nursaimatussadiya; Fitrianingsih, Fitrianingsih; Jayanti, Suci Etri (STIE Bina Karya, 2023)
Micro, small and medium enterprises (MSMEs) are community associations that work and carry out entrepreneurial activities that are closely related to the economic sector. Through MSMEs, it becomes easier for people to collaborate between one community and another. One of the subdistricts that really supports the development of MSMEs is Bagelen Subdistrict. The large number of local MSME actors in the culinary sector is considered to have greatly advanced the village economy. But on the other hand, almost every day these MSMEs produce various kinds of waste left over from merchandise production. This problem can be handled by processing waste into creative crafts that have selling value. The aim of the service program is to increase the economic value of waste into additional income for MSMEs. The methods used are socialization, training and marketing assistance. The program results show that MSME waste can be processed into economical knick-knacks in Bagelen Village. These results have implications for increasing the income of MSMEs in Bagelen Village.